Team Virtues and Performance: An Examination of Transparency, Behavioral Integrity, and Trust - Palanski, Michael E.; Kahai, Surinder S.; Yammarino, Francis J. 1954- (2011)
Virtue-based research in business ethics has increased over the last two decades, but most of the research has focused on the actions of an individual person. In this article, we examine the associations among team-level virtues using data from two studies. Specifically, we investigate whether transparency (usually thought to be an organizational- or collective-level construct), behavioral integrity (usually thought to be an individual-level construct), and trust (usually thought to be an individual-level construct) can be conceptualized and operate at the team level of analysis and, if so, what their relationships are to team performance. Using Partial Least Squares (PLS) analysis, we found in both studies that team transparency was positively related to team behavioral integrity, which in turn was positively related to team trust. We also found evidence of a positive relationship between team trust and team performance. Implications of these findings for future teams and ethics research are discussed.
Keywords: Virtues; Trust; Transparency; Teams; Performance; Integrity